Characteristics of Fossil Wood from Loa Tebu Kutai Kertanegara, East Kalimantan - Nani Husien; Muhammad Nur Hidayat; Agus Sulistyo Budi; Erwin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Fossil Wood is wood that has petrified as a result of wood or plant stems being buried by sediment, does not experience decay and the cells in the wood are replaced by minerals over a long period of time but the outer structure of the wood is still maintained. One way to find out the characteristics of fossil wood is by observing or characterizing it both macroscopically and microscopically. This study aims to determine the macroscopic characteristics, hardness values and density of wood fossils found in Loa Tebu Village, Kutai Ketanegara. Observations of macroscopic characteristics included the color of wood fossils which were observed by naked eye and with a loupe magnification of 10x, and observations of other macroscopic characteristics were carried out on three areas of wood namely transverse, tangential and radial planes using a Nikon SMZ 645 Stereo Microscope with a magnification of 30x. The hardness value uses a rock hardness test tool, namely